Measuring multidimensional sustainability in small-scale aquaculture: evidence from the Gulf of Nicoya, Costa Rica - Robles-Herrera, Ana; Guzmán Hernández, Tomás de Jesús; Herrera-Ulloa, Ángel; Radrigan, Rudi; Brugarolas, Margarita (Frontiers in Sustainable Food Systems, 2025)
IntroductionThe United Nations Development Programme has been instrumental in promoting the generation of productive activities that respond to a sustainable production model. In this regard, small-scale aquaculture merits particular attention for its demonstrated propensity towards sustainability. The present study analyses the levels of multidimensional sustainability through a case study of a small-scale aquaculture system, utilising a measurement system with indicators.Materials and methodsInformation was collected through the application of a measurement instrument during visits to oyster and shrimp farms. The evaluation process involved the analysis of 36 indicators, which were distributed across 12 sustainability variables. These variables addressed the technical, economic, social, environmental and governance dimensions. The results were analysed separately by species, and the sustainability trends presented were also evaluated.ResultsThe findings indicate that both productive species demonstrate comparable levels of sustainability, exhibiting distinctions across the various dimensions. In terms of both social and economic dimensions, oyster production is the most significant. Conversely, in technical and governance dimensions, shrimp production is the most important. The study revealed discrepancies in the levels of sustainability, which varied according to geographic sector and the organisational structure of the farm. It has been demonstrated that larger farms tend to exhibit a greater degree of sustainability, characterised by extended production times and a family-oriented organisational structure.DiscussionThe analysis of the results addresses the contrasts in the levels of sustainability of shrimp and oyster production in the Gulf of Nicoya, and compares them with similar experiences in other latitudes. It delves into areas of opportunity in the region, such as technification, circular economy and good governance, through the presentation of success stories in other small-scale aquaculture systems around the world. It concludes that the priority areas for management in the region are strengthening the management and planning structure, cohesion and coordination of producer, circular economy model, and designing a specific sustainability index.